2022
DOI: 10.1186/s13690-021-00775-1
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ eating habits in Lebanon during the economic and health crises: a cross-sectional study

Abstract: Background Nurses face multiple stressors that can influence their lifestyle, thus affecting their health status. Scarce are the scientific data on the nutritional status of nurses, especially during health crises. The aim of this study was to assess the impact of the COVID-19 pandemic on the eating habits of hospital nurses in the context of an exceptional economic situation in Lebanon. Methods A cross-sectional study was conducted using a web-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…However, the representation of nurses in this study was low (13.5%) and nursing technician (10.3%) and the specialty of nurses was not reported [29]. Another more recent cross-sectional study investigated the changes in eating habits of 500 hospital nurses in Lebanon [30]. The study found a significant correlation between the reduction of healthy food consumption and stress level.…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the representation of nurses in this study was low (13.5%) and nursing technician (10.3%) and the specialty of nurses was not reported [29]. Another more recent cross-sectional study investigated the changes in eating habits of 500 hospital nurses in Lebanon [30]. The study found a significant correlation between the reduction of healthy food consumption and stress level.…”
Section: Introductionmentioning
confidence: 57%
“…However, the study results were affected by the accompanying economic crisis that impacted the consumption of healthy food. Most participants were bedside nurses (74.8%); however, their specialty unit was not reported [30].…”
Section: Introductionmentioning
confidence: 99%
“…According to the researchers, nurses who worked with COVID-19 patients ate significantly less fruit and vegetables. Additionally, up to 76.2% of nurses declared financial difficulties in buying healthy food [ 35 ]. In another study, most nurses indicated that it is difficult to maintain proper eating habits at work, because the food they often receive from patients as a gift contains a lot of sugar and fat and is easily available [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…McCall et al [49]; Nohra et al [134] Libya (0) Mauritania (0) Morocco ( 7) Bossenbroek and Ftouhi [78]; Bouzidi and Abdellaoui [79]; El Bilali et al [135]; Rachidi et al [136]; Saidi et al [137]; Saidi et al [138]; Sraïri [139] Oman (3) Alazaiza et al [140]; Ben Hassen et al [141]; Mansour et al [142] Qatar (5) Al-Abdi et al [143]; Alah et al [144]; Al-Mulla and Mahfoud [63]; Ben Hassen et al [145]; Kaitibie et al [146] Saudi Arabia (46)…”
Section: Country or Region (Articles Number) Documentsmentioning
confidence: 99%
“…Mosli et al [82]; Mumena [177]; Nohra et al [134]; Olaimat et al [116]; Radwan et al [190]; Radwan et al [191]; Saaty and Aljadani [178]; Sultan et al [180]; Takshe et al [194]; Taybeh et al [119]; Tayyem et al [89]; Tayyem et al [84]; Tayyem et al [85]; Turki et al [187] Food safety Abu Hatab et al [98]; Almanasrah et al [74]; AlTarrah et al [121]; Arfaoui and Alghafari [77]; Dimassi et al [127]; Faour-Klingbeil et al [205]; Faour-Klingbeil et al [94]; Olaimat et al [115];…”
Section: Food Utilisationmentioning
confidence: 99%